Which cocoa bean traits persist when eating chocolate? Real-time nosespace analysis by PTR-QiToF-MS - Acierno, Valentina; Liu, Ningjing; Alewijn, Martin; Stieger, Markus; van Ruth, Saskia M. (Talanta (Oxford), 2019)
More consumers have become aware of the existence of different cocoa genotypes and their origins, which resulted in a growing market of premium chocolates with single-origin beans. The question is whether traits of cocoa botanical and geographical origins still persist in the end product, especially when it is consumed. By analysing the concentrations of volatile organic compounds (VOCs) in the nose of subjects over time while they are eating, new insights about aroma release can be gained. In the current study, in vivo release of VOCs during consumption of dark chocolates with different botanical and geographical origins was examined. Proton Transfer Reaction-Quadrupole interface Time of Flight- Mass Spectrometry (PTR-Qi ToF- MS) was applied to analyse nosespace VOC profiles of 10 subjects while they were eating 10 different chocolates manufactured with beans of different botanical origins (Criollo-Forastero-Trinitario) and geographical origins (Africa-South America-Asia). The headspace of the chocolates were also analysed for comparison. Cocoa botanical information appeared to affect the nosespace profiles more than geographical information. The subjects varied considerable in their VOC release, and inter-individual differences were larger than cocoa beans differences. Nevertheless, the botanical origin was consistently reflected in the nosespace profile during eating. It was clearly possible to distinguish Criollo chocolates from the nosespace profiles despite inter-individual differences. [Display omitted] •Cocoa botanical origin affects in-nose profiles more than geographical origin.•Inter-individual differences are larger than cocoa beans differences.•Criollo chocolates exhibit a distinct in-nose profile.